Feeding dynamics of Cichla kelberi Kullander & Ferreira, 2006 introduced into an artificial lake in southeastern Brazil - Villares Junior, Gilberto Aparecido [UNESP]; Gomiero, Leandro Muller [UNESP] (Sociedade Brasileira de Ictiologia, 2010)
O objetivo desse estudo foi caracterizar sazonalmente a dieta de Cichla kelberi em um lago artificial em Leme-SP, determinando os itens alimentares e as relações com os sexos e com a maturação gonadal dos exemplares amostrados. A dieta de C. kelberi apresenta uma dinâmica em três diferentes períodos: os meses de inverno foram caracterizados por baixa atividade alimentar e alta concentração de peixes indeterminados, durante a primavera ocorreu um aumento na atividade alimentar, sendo Tilapia sp. o item alimentar dominante e durante o verão e início do outono foi evidenciada alta taxa de canibalismo. A plasticidade na composição da dieta foi marcada pela quantidade de presas disponíveis durante os períodos do ano e pelo período reprodutivo.

The objective of this study was to characterize the seasonally of the diet of Cichla kelberi in an artificial lake in Leme-SP, determining the food items and their relation to the sex and gonadal maturity of the fish sampled. The diet of C. kelberi presents a dynamic in three different periods: winter months were characterized by low feeding activity and a high concentration of undetermined fish; increase in feeding activity occurred in the spring, with Tilapia sp. being the dominant food item; and a high rate of cannibalism was observed in the summer and early fall. The plasticity in the composition of the diet was marked by quantity of prey available during the different periods of the year, and the reproductive period.
Keywords: Seasonality; Cannibalism; Predation; Competition